Harmonization of ASEAN Investment Law on the Perspective of Indonesian National Investment Law - Jelly Leviza; Ningrum Natasya Sirait; T. Keizerina Devi (Proceedings of AICS - Social Sciences, 2016)
ASEAN's decision to accelerate the implementation of the ASEAN Economic Community (AEC) by 2015 based on the Cebu Declaration, 2007. ASEAN then create a blueprint that describes the steps that must be reached in the AEC in 2015 such as the elimination of taxes and tariffs based on sectors which have been agreed, and all the factors of production such as labor and capital are allowed to move freely crossed the line of ten member countries through the common market. In the field of investment, ASEAN has an ASEAN Comprehensive Investment Agreement (ACIA) to conduct a review of the Framework Agreement on the ASEAN Investment Area (AIA) and ASEAN Investment Guarantee Agreement (IGA). The establishment of ACIA is to encourage a more liberal investment environment, transparent, competitive and facilitative. Indonesia has been preparing the investment regime under ASEAN for example by creating a variety of legal instruments to further open the influx of foreign investment and ensure equal treatment of foreign investors to domestic investors as desired by the ACIA. The problem today is that besides the existence of ACIA as regional investment agreements under the ASEAN there is also a multilateral investment agreement under the WTO (TRIMs). In most small scale there is also Bilateral  Investment  Treaty  (BIT). That  condition is  still added  to the  national investment regimes of each country, including for example the Indonesian national investment laws. Based on the above, this paper will examine the ASEAN agreement on investment (ACIA) and the Indonesia national legal arrangements. Then it will also examine Indonesian Government policy on BIT with respect to the ACIA. The purpose of this study was to explain the relevance of Indonesia’s national investment law harmonization with ASEAN Agreement and to determine the relevance of the BIT with the ACIA.